Senam Rematik Meningkatkan Jarak Tempuh Berjalan Lansia dengan Nyeri Sendi di Panti Wreda Dharma Bhakti Pajang Surakarta - Tri Susilowati (STIKes Patria Husada Blitar, 2016)
Joint pain experienced by the elderly may limit walking ability like mileage. Mileage can be improved by reducing joint pain through exercise. The purpose of this study was to clarify the effect of rheumatic gymnastics to mileage in older adults with joint pain. This type of research is â€œTrue Experimentalâ€ with The Randomized Pre Test and Post Test Control Group Design. Population is elderly inelderly house of Dharma Bhakti Pajang Surakarta who suffer joint pain and not in a state of total dependency. Sample was elderly who meet the inclusion and exclusion criteria are 40 people (20 people per group). Normality test data used the Kolmogorov-Smirnov test. Analysis of data (pre and post test) with a paired t test (for normal data) and Wilcoxon Signed Ranks Test test (for not normal data) with significance level of 95%. Changes in mileage differences between groups were tested with unpaired t test with significance level of 95%. The results showed mileage in the treatment group experienced an increase, in which the prices are p <0,05. The results of the study data analysis between groups showed that the mileage have p <0,05 (p = 0,022), which means that there are significant differences between groups. It needs a longer time for the adoption and application of the distance so exercise movement performed by the elderly is closer to the direction of movement so that the effect of exercise on mileage is higher.